Phase diagram of bare particles in polymer nanocomposites: Uniting solution and melt blending. (16th September 2021) - Lepcio, Petr; Ondreáš, František; Zárybnická, Klára; Zbončák, Marek; Svatík, Juraj; Jančář, Josef
Abstract: Nanoparticle (NP) spatial arrangement in polymer matrix is a widely investigated scientific issue of great practical importance. The structure of polymer nanocomposites (PNCs) with bare non-grafted NPs are usually evaluated separately for blending in polymer melt and in polymer solution. To the best of our knowledge, no theory of PNC structure has successfully integrated all aspects of solution blending yet, let alone brought a direct comparison of PNC structures prepared by melt and solution blending. In the current study, we for the first time implement the role of solvent into the existing PRISM theory for nanoparticle ordering in polymer melts, compare the theoretical prediction to experimentally prepared structures, and present a united phase diagram for both melt and solution blended PNCs with bare non-grafted NPs. Graphical abstract: Image 1 Highlights: A complex model for structure of solution blended nanocomposites is presented. Experimental results are compared to a phase diagram predicted by the PRISM theory. Solution- and melt-blending is united into a single theory.